2013
DOI: 10.1088/2041-8205/765/1/l9
|View full text |Cite
|
Sign up to set email alerts
|

THE DETECTION OF INTERSTELLAR ETHANIMINE (CH 3 CHNH) FROM OBSERVATIONS TAKEN DURING THE GBT PRIMOS SURVEY

Abstract: We have performed reaction product screening measurements using broadband rotational spectroscopy to identify rotational transition matches between laboratory spectra and the Green Bank Telescope PRIMOS radio astronomy survey spectra in Sagittarius B2 North (Sgr B2(N)).The broadband rotational spectrum of molecules created in an electrical discharge of CH 3 CN and H 2 S contained several frequency matches to unidentified features in the PRIMOS survey that did not have molecular assignments based on standard ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 45 publications
6
101
0
Order By: Relevance
“…In these regions, molecules are often liberated into the gas phase via nonthermal, shock-driven desorption, resulting in colder, spatially extended gas-phase populations that are often more abundant than predicted by standard warm-up models (14). This is consistent with the observation that the structurally similar ethylene oxide is consistently found to have low excitation temperatures (11 to 35 K), well below the temperature of the surrounding grains (15), with the detections of glycolaldehyde (11), ethanimine (16), and propylene oxide's structural isomers propanal (13) and acetone (8), in this region, and with the general pattern of shock-driven liberation of complex molecules in the so-called central molecular zone (14).…”
supporting
confidence: 74%
“…In these regions, molecules are often liberated into the gas phase via nonthermal, shock-driven desorption, resulting in colder, spatially extended gas-phase populations that are often more abundant than predicted by standard warm-up models (14). This is consistent with the observation that the structurally similar ethylene oxide is consistently found to have low excitation temperatures (11 to 35 K), well below the temperature of the surrounding grains (15), with the detections of glycolaldehyde (11), ethanimine (16), and propylene oxide's structural isomers propanal (13) and acetone (8), in this region, and with the general pattern of shock-driven liberation of complex molecules in the so-called central molecular zone (14).…”
supporting
confidence: 74%
“…They recommended that ethanimine from the C 2 H 5 N isomeric group should be a possible interstellar molecule which can be seen in space. Finally, ethanimine has been detected with both the forms in the same sources where methanimine has already been observed (Loomis et al 2013). …”
Section: Introductionmentioning
confidence: 58%
“…From our quantum chemical calculation, we found that E-ethanimine is energetically more stable (4.35 KJ/mol by using MP2/6-311G++(d,p) and 1.2 KJ/mol by using G4 composite method) than Z-ethanimine. Quan et al (2016) and Loomis et al (2013) obtained an energy difference of 4.60 KJ/mol and 4.24 KJ/mol respectively between these two conformers. We have shown the enthalpy of formation values for all the species in Table 2 along with the experimentally obtained values, where available.…”
Section: Ch 5 N Isomeric Groupmentioning
confidence: 96%
“…We do not, however, make the assumption that this temperature is described by local thermodynamic equilibrium (LTE), meaning that the excitation temperature is not thermalized to the kinetic temperature of the gas. This approach has previously proven to be successful in modeling both the emission and absorption of molecules in PRIMOS observations (Hollis et al 2004;Loomis et al 2013;McGuire et al 2016). We note, however, that several other molecules exhibit populations which cannot be described by a single excitation temperature (McGuire et al 2012;Faure et al 2014), and thus care should be taken to examine any single-excitation temperature results on a case-by-case basis.…”
Section: Observationsmentioning
confidence: 99%